Traditional Chinese Medicine for Hashimoto's Thyroiditis: Focus on Selenium and Antioxidant Phytochemicals - Sheng Huang; Panos G. Ziros; Dionysios V. Chartoumpekis; Georgios Psarias; Leonidas Duntas; Xinhe Zuo; Xinyi Li; Zhiguo Ding; Gerasimos P. Sykiotis (MDPI AG, 2024)
Hashimoto's thyroiditis (HT) is not only the most frequent autoimmune thyroid disease (AITD), but it also has a significant impact on patients' health-related quality of life (HRQoL), and it has been variably associated with differentiated thyroid carcinoma. Even though its pathogenesis is still incompletely understood, oxidative stress is believed to play an important role. Hypothyroidism related to later stages of HT can be treated with levothyroxine substitution therapy; various approaches such as selenium supplementation and iodine-restricted diets have been proposed as disease-modifying treatments for earlier stages, and even thyroidectomy has been suggested for refractory cases of painful HT. Nevertheless, many patients still report suboptimal HRQoL, highlighting an unmet medical need in this area. The concepts and approaches of traditional Chinese medicine (TCM) in treating HT are not broadly known in the West. Here, we provide an overview of TCM for HT, including combinations of TCM with selenium. We encompass evidence from clinical trials and other studies related to complex TCM prescriptions, single herbs used in TCM, and phytochemicals; wherever possible, we delineate the probable underlying molecular mechanisms. The findings show that the main active components of TCM for HT have commonly known or presumed antioxidant and anti-inflammatory activities, which may account for their potential utility in HT. Further exploring the practices of TCM for HT and combining them with evidence- and mechanism-based approaches according to Western standards may help to identify new strategies to alter the clinical course of the disease and/or to treat patients' symptoms better and improve their HRQoL.